2018
DOI: 10.3389/fphys.2018.00699
|View full text |Cite
|
Sign up to set email alerts
|

Panax ginseng Polysaccharide Protected H9c2 Cardiomyocyte From Hypoxia/Reoxygenation Injury Through Regulating Mitochondrial Metabolism and RISK Pathway

Abstract: Background and Objective: Ischemic heart disease (IHD) has been the major issue of public health. Panax ginseng (ginseng) has been verified as an effective traditional Chinese medicines and exerted cardioprotective effect. This study aimed to investigate the polysaccharide fraction of ginseng on hypoxia/reoxygenation (H/R) injury in cardiomyocytes and the underlying mechanisms.Methods: Ginseng was extracted by ethanol and fractionated by high-speed counter current chromatography (HSCCC) and column separation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 82 publications
2
23
0
Order By: Relevance
“…The oxygen consumption rate (OCR) and extracellular acidification rate (ECAR) were measured using the Seahorse XFe24 (Seahorse Agilent) extracellular flux analyser, as previously described [22]. Three injections were performed in order to change cells metabolism, namely: oligomycin (1 µg/mL)—a complex V inhibitor; FCCP (3 µM)—a classic uncoupling agent, and antimycin A+Rotenone (2.5 µM + 2 µM)—inhibitors of complex I and III, respectively [23]. The OCR parameters recorded in the analysis were as follows: (i) the basal respiration (before oligomycin addition); (ii) the leak state (after oligomycin addition)—the amount of O 2 consumption needed to sustain the proton gradient; (iii) the maximal respiration (after FCCP addition)—respiration in the presence of a classic uncoupler of oxidative phosphorylation; (iv) the ATP turnover (the difference between the basal respiration and the leak state)—the amount of O 2 consumption used for ATP production; (v) the reserve capacity (the difference between the maximal and the basal respiration).…”
Section: Methodsmentioning
confidence: 99%
“…The oxygen consumption rate (OCR) and extracellular acidification rate (ECAR) were measured using the Seahorse XFe24 (Seahorse Agilent) extracellular flux analyser, as previously described [22]. Three injections were performed in order to change cells metabolism, namely: oligomycin (1 µg/mL)—a complex V inhibitor; FCCP (3 µM)—a classic uncoupling agent, and antimycin A+Rotenone (2.5 µM + 2 µM)—inhibitors of complex I and III, respectively [23]. The OCR parameters recorded in the analysis were as follows: (i) the basal respiration (before oligomycin addition); (ii) the leak state (after oligomycin addition)—the amount of O 2 consumption needed to sustain the proton gradient; (iii) the maximal respiration (after FCCP addition)—respiration in the presence of a classic uncoupler of oxidative phosphorylation; (iv) the ATP turnover (the difference between the basal respiration and the leak state)—the amount of O 2 consumption used for ATP production; (v) the reserve capacity (the difference between the maximal and the basal respiration).…”
Section: Methodsmentioning
confidence: 99%
“…Levels of intracellular and mitochondrial ROS were measured using a DCFH-DA or mitoSOX probe as previously method (Zuo et al, 2018). In brief, at 0, 4, 8, 16, 24, and 48 h after corresponding treatment, cells were harvested, collected, and washed with serum-free DMEM media.…”
Section: Measurement Of Intracellular and Mitochondrial Rosmentioning
confidence: 99%
“…Mitochondrial respiration is an indicator of both the functional bioenergetics capacity of mitochondria and overall cellular health (Zuo et al, 2018;Pan et al, 2018). In the study, we used an XFp Extracellular Flux Analyzer (Seahorse Biosciences, North Billerica, MA, USA) to evaluate the OCR.…”
Section: Evaluation Of Ocr and Ecarmentioning
confidence: 99%
“…However, the injury caused by hypoxia may be averted. A recent study performed by Zuo et al showed that an acid polysaccharide fraction of ginseng (AP1) was the most effective fraction at protecting cardiomyocytes from hypoxia [135]. AP1 exerted a protective effect by increasing the expression of both GR and the estrogen receptor, which in turn mediated the activation of the RISK pathway and eNOS-dependent mechanisms to resist reperfusion injury [136].…”
Section: The Role Of Gr In Cardiovascular Diseasesmentioning
confidence: 99%